The Effectiveness of Vermicompost and NPK Fertilizer Treatment on Cucumis melo L. Vegetative Growth - Raksun, Ahmad; Ilhamdi, Moh. Liwa; Merta, I Wayan; Mertha, I Gde (Jurnal Biologi Tropis, 2024)
Melon is an annual plant, growing creeping with a stem length of about 3 meters. The vegetative and generative growth of melons is influenced by genetic and environmental factors. Environmental factors that affect the growth of melons include the abundance of nutrients in the growing media. Research has been carried out on the effectiveness of vermicompost and NPK fertilizer treatment on melon vegetative growth, with the aim of analyzing the effectiveness of vermicompost in increasing stem length, number, length and width of leaves and stem diameter of melons. effectiveness of NPK fertilizer in increasing stem length, number, length and width of leaves and stem diameter of melons. Effectiveness of the interaction of vermicompost and NPK fertilizer in stimulating melon growth. Growth parameters were measured when the melon was 28, 29 and 30 days after planting, the data obtained was analyzed using Anova. The results showed that vermicomposti is effective in increasing stem length, total and leaf length, but is not effective in increasing leaf width and stem diameter of melons. Application of NPK fertilizer is effective in increasing stem length, total leaves, leaf length, leaf width and stem diameter of melon. The interaction between vermicompost and NPK fertilizer was not effective in stimulating melon growth.